Quantifying the Spillovers from China Rebalancing Using a Multi-Sector Ricardian Trade Model - Mano, Rui. (Washington, D.C. : International Monetary Fund, 2016)
This paper assesses the spillovers from different facets of China rebalancing using a calibrated Ricardian trade model that includes 41 economies, each consisting of 34 sectors. We find that China's move up the value chain in particular has the potential for significant spillovers - on the one hand, adversely affecting industrialized economies heavily involved in the Asia value chain, while at the same time generating positive spillovers to lower and middle income countries. The model's strength lies in endogenously capturing production value chains and international trade of goods across sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet